2019
DOI: 10.1038/s41598-019-50545-x
|View full text |Cite
|
Sign up to set email alerts
|

Oral Anti-Tumour Necrosis Factor Domain Antibody V565 Provides High Intestinal Concentrations, and Reduces Markers of Inflammation in Ulcerative Colitis Patients

Abstract: V565 is an engineered TNFα-neutralising single domain antibody formulated into enteric coated mini-tablets to enable release in the intestine after oral administration as a possible oral treatment for inflammatory bowel disease (IBD). Following oral administration, ileal recovery of V565 was investigated in four patients with terminal ileostomy. Intestinal and systemic pharmacokinetics were measured in six patients with Crohn’s disease and evidence of target engagement assessed in five patients with ulcerative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Oral delivery of anti-CD3 monoclonal antibodies has been shown to have a biological effect in both preclinical (36,37) and clinical (38) settings, although a relatively small fraction of the dosed antibody reached the small intestine in an active form (36). A llama domain antibody engineered for enhanced protease stability has shown promising anti-inflammatory activity in a small cohort of IBD patients (39). There remains a major unmet need to be able to orally administer antibody therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…Oral delivery of anti-CD3 monoclonal antibodies has been shown to have a biological effect in both preclinical (36,37) and clinical (38) settings, although a relatively small fraction of the dosed antibody reached the small intestine in an active form (36). A llama domain antibody engineered for enhanced protease stability has shown promising anti-inflammatory activity in a small cohort of IBD patients (39). There remains a major unmet need to be able to orally administer antibody therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…Serum concentrations of V565 were also observed in this study, showing that V565 is partly absorbed after oral administration. V565 has been investigated in a clinical study [ 104 ] and is discussed in Section 4 .…”
Section: Preclinical Studies On Local Tnf-α Inhibitionmentioning
confidence: 99%
“…[ 92 , 94 ]. Results from a clinical trial [ 104 ] showed that active V565 could be recovered in the ileal fluids of patients with a terminal ileostomy after oral administration of enteric-coated tablets with a pH threshold ≥ 6. In CD patients, high active V565 concentrations could be recovered in fecal samples.…”
Section: Clinical Studies On Local Tnf-α Inhibitionmentioning
confidence: 99%
“…Eudragit-coated V565 was encapsulated in hydroxypropyl methylcellulose (HPMC) capsules. Overall, this study showed that oral-delivered active V565 reaches IBD disease sites in high concentrations and can bind to V565 TNF-α + cells in UC lesions (Nurbhai et al, 2019). In another phase I clinical study, 47 patients with CD were involved in investigating tolerability and safety of oral V565, and V565 is currently under phase II clinical study in Europe and North America (Crowe et al, 2017).…”
Section: Oral Delivery Of Biologics In Ibd Treatment Monoclonal Antibodiesmentioning
confidence: 78%
“…V565 is a 12.6-kDa anti-TNF-α heavy chain variable domain antibody. It is isolated from a phage library produced from lymphocytes of a human TNF-α hyperimmunized llama and engineered to be resistant to intestinal and inflammatory proteases while retaining the TNF-α neutralizing potency against both soluble and membrane forms of human TNF-α ( Crowe et al, 2017 ; Nurbhai et al, 2019 ). Opposite to AVX-470, V565 is unable to survive in acidic stomach environment and requires sustenance from oral delivery vehicles.…”
Section: Oral Delivery Of Biologics In Ibd Treatmentmentioning
confidence: 99%